Javanese Culture-based Islamic Education Model at the Yogyakarta Wayang Kekayon Khalifah Performance - Hidayat, Kun; Lutfianto, Lutfianto (Early Publishing, 2025)
This research is motivated by the lack of a study of the Javanese culture-based Islamic education model in the community. One of the severity of the existing problems is the fading of molimo teachings in Javanese society, such as the prohibition of drunkenness, adultery, consuming illegal drugs, stealing, and gambling. The purpose of this study is to analyze how Islamic education is based on Javanese culture, as well as to analyze the internalization and adaptation of the cultural value of the art of Wayang Kekayon Khalifah in the performance of Wayang Kekayon Khalifah. This research method uses a qualitative type of case study, in order to systematically organize the flow of this research, so as to answer the formulation of the problem. The results of this study include the formulation of a Javanese culture-based Islamic education model in the performance of Wayang Kekayon Khalifah including adaptive to local wisdom, dialogue on Javanese culture and Islamic religion, transforming towards Islamic living rules, and communicative in answering local community issues. So that the formulation of the model can be an alternative in overcoming the shift in the character of Javanese society.